Business is good F. Scott Fitzgerald, professional writer - West, James L. W. 1946- (Penn State University Press, 2023)
Widely regarded as one of America's great authors, F. Scott Fitzgerald led a life of drama and extravagance that often overshadowed his writing career. This book refocuses attention on how Fitzgerald viewed and approached the business of writing. Fitzgerald scholar James L. W. West III explores the writer's professional life through personal letters, manuscripts, his business ledger, editions of his novels, and even a "seven-year plan." In assessing these diverse materials, West reveals fascinating details about what led Fitzgerald to follow authorship as a calling, why he took on certain projects, how he managed his finances, and what influenced his writing style. Connecting Fitzgerald's career to his literary texts, West also provides new information on the development and publication history of some of Fitzgerald's most important works, such as The Great Gatsby and Jacob's Ladder. Throughout, West pays close attention to the delicate balance in Fitzgerald's career between money and literary respectability, commerce and art.A keen, engaging, and intimate look at Fitzgerald's day-to-day work of writing for a living, Business Is Good is a must-have for anyone who wants a better understanding of this American literary giant